Determinants of state property management: Moderating role of internal control system - Dewabrata, Christian; Firmansyah, Amrie (Journal of Accounting and Investment, 2024)
Research aims: This study examines the effect of employee competence, organizational commitment, and information systems on the quality of state property management with the Government Internal Control System (GICS) as a moderating variable at the Ministry of Law and Human Rights of the Republic of Indonesia.Design/Methodology/Approach: This research used data from 205 State Property Operators at Indonesia's Ministry of Law and Human Rights. Data analysis in this study employed the Structural Equation Modeling (SEM) method, in which hypothesis testing was carried out using the bootstrapping analysis.Research findings: The results of this study indicate that while employee competence and information systems positively affected the quality of state property management, organizational commitment did not affect the quality of state property management. Furthermore, GICS could weaken the positive effect of employee competence on the quality of state property management, and GICS could strengthen the positive effect of information systems on the quality of state property management. However, GICS failed to moderate the relationship between organizational commitment and the quality of state property management.Theoretical contribution/Originality: This research provides a conceptual framework that guides other studies in Indonesian state property management, which has rarely been examined in previous studies. Practitioner/Policy implication: This research contributes to the preparation of better work programs, procedures, and supervision within the Ministry of Law and Human Rights to create state property management that is legal, administrative, and physically orderly.